Pathogenicity of entomopathogenic Beauveria bassiana strains on Helicoverpa armigera (Hübner) - Boulamtat, Rachid; El-Fakhouri, Karim; Jaber, Hassna; Oubayoucef, Ali; Ramdani, Chaimae; Fikraoui, Nabil; Al-Jaboobi, Muamar; El Fadil, Meryem; Maafa, Ilyass; Mesfioui, Abdelhalem; Kemal, Seid Ahmed; El Bouhssini, Mustapha (Frontiers Media, 2025)
The destructive pest of chickpeas, Helicoverpa armigera (Hübner), is difficult to control using synthetic insecticides. The current research examined the entomopathogenic and endophytic colonisation effects of three fungal strains of Beauveria bassiana (HASS; RFSL10; SP-IR-566) against H. armigera larvae under laboratory, greenhouse, and field conditions. Four inoculation methods were used in the greenhouse: Root Dipping (RD), Leaf Spraying (LS), Stem Injection (SI), and Seed Coating (SC), while spray application was used for laboratory and field treatments. Under laboratory conditions, the highest entomopathogenic effect was recorded by HASS and RFSL10 strains applied as a direct spray at 108 conidia mL-1 with 100% mortality, followed by SP-IR-566 with 96%, 12 days after treatment. Furthermore, foliar application in the field reduced larval population by an average ranging from 82 to 100%, confirming the significant effects of the three tested strains. In terms of endophytic colonisation under greenhouse setting, both stem injection and root dipping methods expressed low to moderate mortality rates ranging from 32 to 40%, 15 days after application. These findings suggested that B. bassiana strains, investigated as foliar application, had a potential as an effective strategy to control H. armigera. This study also offers new insights into the potential of the endophytic entomopathogens approach as a viable and safe alternative to chemical pesticides.